denae24
contestada

Given that f(x) = x2 –3x – 40 and g(x) = x +5, find (f +g)(x) and express
the result in standard form.

Respuesta :

Answer:

[tex](f+g)(x)=x^2-2x-35[/tex]

Step-by-step explanation:

So we have the two functions:

[tex]f(x)=x^2-3x-40\text{ and } g(x)=x+5[/tex]

And we want to find (f+g)(x). This is the same as:

[tex](f+g)(x)=f(x)+g(x)[/tex]

Substitute:

[tex]=(x^2-3x-40)+(x+5)[/tex]

Combine like terms:

[tex]=x^2+(-3x+x)+(-40+5)[/tex]

Add:

[tex]=x^2-2x-35[/tex]

And we're done!

ACCESS MORE